Information Circular 44. Geochemical Evaluation of Platinum Group Element (PGE) Mineralization in the Sonju Lake Intrusion, Finland, Minnesota - Miller, James D., Jr. (Minnesota Geological Survey, 1999)
This study was undertaken to evaluate the potential for stratiform platinum group element (PGE) mineralization in the Sonju Lake intrusion (SLI). The SLI is a well differentiated, tholeiitic, mafic layered intrusion that is part of the multiple intrusive Beaver Bay Complex, and is exposed near Finland, Minnesota. Geochemical analyses of outcrop and drill-core samples that span the 1200-m-thick SLI were interpreted in the context of (1) data from PGE reefs in other tholeiitic layered intrusions (most notably the Skaergaard intrusion of East Greenland), and (2) models of PGE and sulfide mineralization in tholeiitic intrusions. The geochemical data show that a PGE-mineralized horizon is present approximately two-thirds of the way up from the base of the moderately south-dipping, sheet-like SLI. PGE mineralization was apparently related to initial sulfide saturation and subsequent exsolution of sulfide melt from the SLI magma. The data also indicate that as it settled, the sulfide melt efficiently scavenged PGEs from the SLI magma, and concentrated them into a relatively narrow interval of gabbroic cumulates. The geochemical signature of the SLI is remarkably similar to that of the PGE-bearing Platinova reef in the Skaergaard intrusion. The highest Pd, Pt and Au concentrations in SLI outcrop samples are far from economic grade (360, 66, and 85 ppb respectively); but a more precise evaluation of peak grade, thickness, and lateral continuity requires drilling and analysis of the entire interval. When the results of the study reported here are combined with evidence for similar mineralization in the Layered Series at Duluth, they indicate that tholeiitic layered intrusions of the Duluth and Beaver Bay complexes are favorable exploration targets for reef-type PGE mineralization.